Flood exposure and social vulnerability in the United States - Tate, Eric; Rahman, Asif; Emrich, Christopher T.; Sampson, Christopher C. (Natural Hazards, 2021)
Human exposure to floods continues to increase, driven by changes in hydrology and land use. Adverse impacts amplify for socially vulnerable populations, who disproportionately inhabit flood-prone areas. This study explores the geography of flood exposure and social vulnerability in the conterminous United States based on spatial analysis of fluvial and pluvial flood extent, land cover, and social vulnerability. Using bivariate Local Indicators of Spatial Association, we map hotspots where high flood exposure and high social vulnerability converge and identify dominant indicators of social vulnerability within these places. The hotspots, home to approximately 19 million people, occur predominantly in rural areas and across the US South. Mobile homes and racial minorities are most overrepresented in hotspots compared to elsewhere. The results identify priority locations where interventions can mitigate both physical and social aspects of flood vulnerability. The variables that most distinguish the clusters are used to develop an indicator set of social vulnerability to flood exposure. Understanding who is most exposed to floods and where, can be used to tailor mitigation strategies to target those most in need.
MAG ID: 3119415889

A place-based model for understanding community resilience to natural disasters - Cutter, Susan L.; Barnes, Lindsey; Berry, Melissa; Burton, Christopher; Evans, Elijah; Tate, Eric; Webb, Jennifer (Global Environmental Change, 2008)